2005
DOI: 10.1198/016214504000001015
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear Mixed-Effects Models for Dyadic Data

Abstract: This article discusses the use of a symmetric multiplicative interaction effect to capture certain types of third-order dependence patterns often present in social networks and other dyadic datasets. Such an effect, along with standard linear fixed and random effects, is incorporated into a generalized linear model, and a Markov chain Monte Carlo algorithm is provided for Bayesian estimation and inference. In an example analysis of international relations data, accounting for such patterns improves model fit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
359
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(364 citation statements)
references
References 21 publications
1
359
0
Order By: Relevance
“…We apply an existing statistical SNA framework (13) known as latent space modeling (7,8) to analyze eight empirical trophic food webs that have been previously studied (14). These webs were observed from Goose Creek Bay in the St. Marks National Wildlife Refuge in the southeastern United States (15), the Benguela marine ecosystem off the South African coast (16), the grasslands in England and Wales (17), the Caribbean coral reefs with a reduced set of nodes (18), the northeast US continental shelf (19), a pond on Skipwith Common in England (20), the Caribbean island of St. Martin (21), and Ythan Estuary in Scotland (22).…”
mentioning
confidence: 99%
“…We apply an existing statistical SNA framework (13) known as latent space modeling (7,8) to analyze eight empirical trophic food webs that have been previously studied (14). These webs were observed from Goose Creek Bay in the St. Marks National Wildlife Refuge in the southeastern United States (15), the Benguela marine ecosystem off the South African coast (16), the grasslands in England and Wales (17), the Caribbean coral reefs with a reduced set of nodes (18), the northeast US continental shelf (19), a pond on Skipwith Common in England (20), the Caribbean island of St. Martin (21), and Ythan Estuary in Scotland (22).…”
mentioning
confidence: 99%
“…This formulation of latent space is inherently symmetrical 64 . Previously, we have shown that this latent space model accurately predicts cactus bug movements 21 .…”
Section: Methodsmentioning
confidence: 99%
“…where K is the number of dimensions in the Euclidean latent space (we set K ¼ 2) 63,64 . This formulation of latent space is inherently symmetrical 64 .…”
Section: Methodsmentioning
confidence: 99%
“…If a threshold function is used instead, the graph model corresponds to the random geometric graph model discussed in the next section. Extensions of this model can be found in [11,15,24].…”
Section: Spatial Models With Network-based Link Formationmentioning
confidence: 99%